A new index based on mechatronics abilities for the conceptual design evaluation. (February 2018) - Moulianitis, V.C.; Zachiotis, G.-A.D.; Aspragathos, N.A.
Abstract: In this paper, a new mechatronics index is proposed for the evaluation of the alternatives in the conceptual design phase. The criteria aggregated to the index are acquired mostly by the collective knowledge presented in the Multi Annual Roadmap for robotics in Europe and adapted by considering the recent advancements in mechatronics. The mathematical formulation of this design index is based on the discrete Choquet integral, taking into account the interactions among the criteria. An application of the proposed mechatronics index to the design of an educational firefighting robot is presented as a case study to demonstrate the support to the designers in the conceptual design evaluation process.